2017
DOI: 10.1590/s0102-865020170120000003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different commercial fat sources on brain, liver and blood lipid profiles of rats in growth phase

Abstract: Purpose: To investigate the fatty acid content of different fat sources and evaluate the effect of them on plasma and hepatic lipids and on the fatty acid profile of the brain tissue of Wistar rats. Methods: Thirty male albino Wistar rats received for 59 days, the following diets: diet added of margarine with low content of polyunsaturated fatty acids (PUFA); diet added of margarine with high content of PUFA; diet added of butter; diet added of hydrogenated vegetable fat; diet added of soybean oil. Fatty acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Some studies reported that dietary interventions might change lipid contents in the brain [47,48]. This is consistent with our results since more than half of the brain fatty acid levels were significantly different among groups.…”
Section: Discussionsupporting
confidence: 93%
“…Some studies reported that dietary interventions might change lipid contents in the brain [47,48]. This is consistent with our results since more than half of the brain fatty acid levels were significantly different among groups.…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, there are many reports showing that different classes of fatty acids from diet can produce various hypercholesterolaemia states (de Angelis-Pereira et al. 2017 ). Magri-Tomaz et al.…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to the research by Franczyk-Żarów et al and de Angelis-Pereira et al which showed that margarine administration was able to significantly increase TG levels in experimental animals. Meanwhile, liquid butter was able to lower HDL levels better than liquid margarine [15], [16]. Atherogenic index is a potential marker for metabolic-related diseases.…”
Section: Resultsmentioning
confidence: 99%